iwCLL guidelines for diagnosis, indications for treatment, response assessment, and supportive management of CLL - Hallek, Michael; Cheson, Bruce D.; Catovsky, Daniel; Caligaris-Cappio, Federico; Dighiero, Guillermo; Döhner, Hartmut; Hillmen, Peter; Keating, Michael; Montserrat, Emili; Chiorazzi, Nicholas; Stilgenbauer, Stephan; Rai, Kanti R.; et al. (Blood, 2018)
The previous edition of the consensus guidelines of the International Workshop on Chronic Lymphocytic Leukemia (iwCLL), published in 2008, has found broad acceptance by physicians and investigators caring for patients with CLL. Recent advances including the discovery of the genomic landscape of the disease, the development of genetic tests with prognostic relevance, and the detection of minimal residual disease (MRD), coupled with the increased availability of novel targeted agents with impressive efficacy, prompted an international panel to provide updated evidence- and expert opinion–based recommendations. These recommendations include a revised version of the iwCLL response criteria, an update on the use of MRD status for clinical evaluation, and recommendations regarding the assessment and prophylaxis of viral diseases during management of CLL.